Concussions and Capital: Tom Brady, CTE, and the NFL's Crisis of Identity. (December 2019) - Siegel, Brett
Chronic traumatic encephalopathy (CTE)–related research has threatened the NFL's reputation, the prospects of its labor pool, and its most dominant mythologies. To survive this crisis, the league must assuage the concerns of current and aspiring players as well as disillusioned fans. Although the NFL claims to be mitigating its embedded violence, it reflexively clings to its identity as a bastion for militarized and nationalized masculinity. Gisele Bündchen's comments that her husband Tom Brady suffers regular concussions elicited a momentary rupture for a sports media landscape tasked with suturing the hegemonic, heteronormative, and racialized narratives crucial to the NFL brand. The ensuing project to realign the meanings of a valuable celebrity, commodity, and symbolic text elides and marginalizes those who are most vulnerable in the concussion crisis.